ANALISA TINGKAT PELANGGARAN HUKUM DI LAUT INDONESIA MENGGUNAKAN METODE TRIPLE EXPONENTIAL SMOOTHING - markus - tukan; Heru Lumaksono; Syariful Alim; Hozairi Hozairi (Jurnal Aplikasi Teknologi Informasi dan Manajemen (JATIM), 2020)
Violation of the law at sea is one indicator to measure the security level of a country. To maintain security stability at sea in Indonesia, the Government needs to forecast the number of violations of the law at sea to determine the next policy. Forecasting is a picture of events that will occur in the future. The method used to predict law violations in the Indonesian seas is the Triple Exponential Smoothing (TES) Hold-Winters, the TES method is a pretty good forecasting method for long-term, medium-term and short-term forecasting. The processed data is data on law violations in the Indonesian seas from 1996 to 2019 from the Indonesian Maritime Security Agency. The results obtained from this study are the results of the analysis of the level of accuracy of the MAD, MSE, MAPE, MSE and RMSE data to find the smallest error value. The results of the study have predicted the number of law violations at sea in Indonesia in the next five years will decrease with forecasting values ​​(94 86 79 71 61) with a constant value of alpha = 0.9, beta = 0.2, and theta = 0.1 and the average value absolute percentage error (MAPE = 3,%) and mean root error value (RMSE = 6.38). The contribution of this research can be considered by Bakamla to set up a joint operations strategy with other institutions that have legal authority in the Indonesian seas.